Coupled hydrological and biogeochemical processes controlling variability of nitrogen species in streamflow during autumn in an upland forest. Issue 2 (24th February 2014) - Sebestyen, Stephen D.; Shanley, James B.; Boyer, Elizabeth W.; Kendall, Carol; Doctor, Daniel H.
Abstract: Autumn is a season of dynamic change in forest streams of the northeastern United States due to effects of leaf fall on both hydrology and biogeochemistry. Few studies have explored how interactions of biogeochemical transformations, various nitrogen sources, and catchment flow paths affect stream nitrogen variation during autumn. To provide more information on this critical period, we studied (1) the timing, duration, and magnitude of changes to stream nitrate, dissolved organic nitrogen (DON), and ammonium concentrations; (2) changes in nitrate sources and cycling; and (3) source areas of the landscape that most influence stream nitrogen. We collected samples at higher temporal resolution for a longer duration than typical studies of stream nitrogen during autumn. This sampling scheme encompassed the patterns and extremes that occurred during base flow and stormflow events of autumn. Base flow nitrate concentrations decreased by an order of magnitude from 5.4 to 0.7 µmol L −1 during the week when most leaves fell from deciduous trees. Changes to rates of biogeochemical transformations during autumn base flow explained the low nitrate concentrations; in‐stream transformations retained up to 72% of the nitrate that entered a stream reach. A decrease of in‐stream nitrification coupled with heterotrophic nitrate cycling were primary factors in the seasonal nitrate decline. The period of low nitrate concentrations ended with a storm event in which stream nitrate concentrations increased by 25‐fold. In the ensuing weeks, peak stormflow nitrate concentrations progressively decreased over closely spaced, yet similarly sized events. Most stormflow nitrate originated from nitrification in near‐stream areas with occasional, large inputs of unprocessed atmospheric nitrate, which has rarely been reported for nonsnowmelt events. A maximum input of 33% unprocessed atmospheric nitrate to the stream occurred during one event. Large inputs of unprocessed atmospheric nitrate show direct and rapid effects on forest streams that may be widespread, although undocumented, throughout nitrogen‐polluted temperate forests. In contrast to a week‐long nitrate decline during peak autumn litterfall, base flow DON concentrations increased after leaf fall and remained high for 2 months. Dissolved organic nitrogen was hydrologically flushed to the stream from riparian soils during stormflow. In contrast to distinct seasonal changes in base flow nitrate and DON concentrations, ammonium concentrations were typically at or below the detection limit, similar to the rest of the year. Our findings reveal couplings among catchment flow paths, nutrient sources, and transformations that control seasonal extremes of stream nitrogen in forested landscapes. Key Points: Stream nitrate during autumn varied with inputs of atmospheric nitrate Autumn leaf fall and stormflow events affected stream nitrate and DON dynamics Stream nitrate and DON during autumn storms originated from riparian areas not hillslopes